FACTORS OF DEVELOPMENT OF CREATIVE THINKING OF PERSONALITY IN UNIVERSITY ENVIRONMENT (ON THE EXAMPLE OF OUTSTANDING SCIENTISTS) - Виноградова, Вікторія Євгенівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2020)
The article reveals the complex process of formation and development of future scientists’ creative personality. The main purpose of the article is to study the main factors of formation and development of creative thinking of V. Vernadsky, I. Mechnykov and K. Ushynsky in the process of their studies at university. Theoretical and biographical were methods used in the article. The main factors of outstanding scientists’ creative thinking formation have been analysed. The research focuses on university environment of the scientists. Attention was paid to the microenvironments of V. Vernadsky, I. Mechnykov and K. Ushynsky. The educational conditions, which can become efficient in the formation of a personality’s creative thinking have been analysed. The directions for the development of scientific thinking of students as creative persons have been provided. As a result, the main factors influencing the development of a personality’s creative thinking during his or her studies at university have been specified. The factors affecting the formation of scientific talent in the conditions of ordinary life of V. Vernadsky, I. Mechnykov and K. Ushynsky have been considered. The main factors that influenced the development of creative thinking of the outstanding scientists are the following: a high level of general abilities which is manifested in learning abilities; the influence of prominent scientists of that time who taught at university; a high level of motivation and constant self-development of the future scientists; the ability to choose one’s own trajectory and pace of learning independently. In the article attention is paid to the subject-value approach in the development of a personality’s creative thinking. Psychological and pedagogical principles for the implementation of the concept of creative abilities development have been indicated, the conditions for the organization of a developing environment, creation of favourable conditions for the development of creativity in scientific activity have been considered. So, micro- and macroenvironments are inherent in the reality where the development of a personality’s creative thinking takes place. The formation of a personality’s creative thinking is influenced by the close university environment and other systems of the macroenvironment. However, self-development and a high level of motivation towards professional determination and realization are extremely important